STEM INTEGRATED CHEMISTRY LEARNING EFFECTIVENESS (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) IN THE TIME OF COVID-19 - Fatayah Fatayah; Ika Farida Yuliana; Rendy Priyasmika (Universitas Negeri Surabaya, 2022)
Abstract. The purpose of this study was to determine the effectiveness of STEM (Science, Technology, Engineering, and Mathematics) integrated learning on the material of molecular form for Class X MA Al-Khoiriyah students. The research design used in this research is descriptive analysis. The stages of this research consist of 3 (three) stages, namely pre-research, testing the validation of research tools, and implementing STEM integrated learning. As for knowing the effectiveness is measured by indicators, namely the level of student learning completeness after integrated STEM learning activities and the resulting STEM products. From the analysis of the final test, it can be seen that of the ten students who were the research subjects, 80% had achieved completeness and the resulting STEM product was in the good category so it can be concluded that STEM integrated learning is effectively used in molecular geometry learning. Keywords: Effectiveness, STEM, Chemistry, Molecular geometry